Investigation of DNA Damage and Apoptosis in Bovine Ocular Squamous Cell Carcinoma - Muhammet Bahaeddin Dörtbudak; Kerem Yener (Veterinary Medicine and Science)
ABSTRACT Ocular squamous cell carcinoma represents the most prevalent form of cancer in cattle and exerts a deleterious effect on animal welfare and breeders. This study sought to elucidate the relationship between DNA damage and apoptosis with the aim of advancing our understanding of the pathogenesis of the disease. Nine bovine tissue samples with suspected ocular squamous cell carcinoma (OSCC) were examined histopathologically and immunohistochemically. The taken tissue samples, in histopathological examinations by haematoxylin‐eosin (HE), staining revealed the presence of neoplastic cells exhibiting various grades of differentiation. It observed the presence of polygonal or ovoid‐shaped cells with hyperchromatic nuclei and vesicular cytoplasm, as well as mitotic figures and bizarre giant cells. Islets and caudal extensions of the tumour cells were observed to contain keratin deposits. Immunohistochemical staining of OSCC tissues was performed using γ‐H2AX for DNA double‐strand breaks, 8‐OHdG for DNA oxidation and CASP‐3 biomarkers for nuclear apoptosis. The immunohistochemical examination demonstrated that the expression of 𝛾‐H2AX and 8‐OHdG was markedly elevated, while CASP‐3 expression was relatively diminished in aggressive tumours. In contrast, the opposite was observed in low‐grade tumours. This study is the first to report DNA double‐stranded breaks in eye cancers, and it has also shown that DNA helix breaks and guanine oxidation are effective in cancer pathogenesis. It has also been determined that apoptotic defence reactions due to DNA damage are reduced. In light of these findings, we made a significant contribution to the development of BOSCC carcinogenesis.